CRISPR/Cas9-Mediated Three Nucleotide Insertion Corrects a Deletion Mutation in MRP1/ABCC1 and Restores Its Proper Folding and Function - Qinqin Xu; Yue-xian Hou; Xiu-bao Chang (Elsevier, 2017)
A three-nucleotide deletion in cystic fibrosis transmembrane conductance regulator/ATP-binding cassette transporter C7 (CFTR/ABCC7) resulting in the absence of phenylalanine at 508 leads to mis-fold of the mutated protein and causes cystic fibrosis. We have used a comparable three-nucleotide deletion mutant in another ABCC family member, multidrug resistance-associated protein (MRP1)/ABCC1, to determine whether CRISPR-Cas9-mediated recombination can safely and efficiently knock in three-nucleotide to correct the mutation. We have found that the rate of homology-directed recombination mediated by guideRNA (gRNA) complementary to the deletion mutant is significantly higher than the one mediated by gRNA complementary to the wild-type (WT) donor. In addition, the rate of homology-directed recombination mediated by gRNA complementary to the WT donor is significantly higher than that of gRNAs complementary to the 5' or 3' side of the deletion mutant. Interestingly, the frequency of mutations introduced by gRNA complementary to the deletion mutant is significantly higher than with gRNA complementary to WT donor. However, combination of gRNAs complementary to both WT donor and deletion mutant decreased the rate of homology-directed recombination, but did not significantly decrease the mutation rate introduced by this system. Thus, the data presented here provide guidance for designing of gRNA and donor DNA to do genome editing, especially to correct the mutations with three mismatched nucleotides, such as three-nucleotide deletion or insertion.